2018
DOI: 10.1017/9781108436427
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure Development and Ape Conservation

Abstract: Infrastructure development in Africa and Asia is expanding at breakneck speed, largely in biodiversity-rich developing nations. The trend reflects governments' efforts to promote economic growth in response to increasing populations, rising consumption rates and persistent inequalities. Large-scale infrastructure development is regularly touted as a way to meet the growing demand for energy, transport and food-and as a key to poverty alleviation. In practice, however, road networks, hydropower dams and "develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 324 publications
(600 reference statements)
0
2
0
Order By: Relevance
“…Where forests are cleared for agriculture, agro-forestry, natural resource extraction, or human settlements, orangutans are often driven out of their original habitats or have easier access to human crops ( 94 96 ). This can lead to conflicts with people when orangutans are found crop foraging or using human-occupied areas.…”
Section: Discussionmentioning
confidence: 99%
“…Where forests are cleared for agriculture, agro-forestry, natural resource extraction, or human settlements, orangutans are often driven out of their original habitats or have easier access to human crops ( 94 96 ). This can lead to conflicts with people when orangutans are found crop foraging or using human-occupied areas.…”
Section: Discussionmentioning
confidence: 99%
“…Orangutans are referred to as the ‘umbrella’ species because their existence could serve as a healthy indicator for protected forests and natural conservation areas. The World Bank reports based on previous monitoring activities in Africa and South America showed that the improved road-access and facilities that facilitates natural habitat degradations, particularly within the NP and its peripheries, and also the Soraya Park ( Arcus Foundation 2018 ). A sign of ‘political changing will’ was prepared by the Ministry of Forestry, with contributions from a few renowned orangutans’ experts.…”
Section: Discussionmentioning
confidence: 99%